Xanthoceraside Could Ameliorate Alzheimer’s Disease Symptoms of Rats by Affecting the Gut Microbiota Composition and Modulating the Endogenous Metabolite Levels - Zhou, Hongxu; Tai, Jingjie; Xu, Haiyan; Lu, Xiumei; Meng, Dali (Frontiers in Pharmacology, 2019)
Xanthoceraside (XAN) is a natural-derived compound with anti-Alzheimer activity from the husks of Xanthoceras sorbifolia. Although its therapeutic effect had been confirmed in previous studies, the mechanism was still unclear due to its poor solubility and low permeability. In this study, the pharmacological effect of XAN on Alzheimer’s disease (AD) was confirmed by behavior experiments and H&E staining observation. Fecal microbiota transplantation (FMT) experiment also replicatedthe therapeutic effects, which indicating the potential targets of XAN on gut microbiota. The sequencing of 16S rRNA genes in fecal samples demonstrated that XAN reversed gut microbiota dysbiosis in AD animals. XAN could change the relative abundances of several phyla and genus of bacterial, particularly the ratio of Firmicutes/Bacteroidetes. Among them, Clostridium IV, Desulfovibrio, Corynebacterium and Enterorhabdus, had been reported to be involved in the pathologic developments of AD and other central nervous system disease. In metabolomics study, a series of host endogenous metabolites were detected, including amino acids, lysophosphatidylcholine, dihydrosphingosine, phytosphingosine, inosine and hypoxanthine, which were all closely associated with the development of AD. Combined with the Spearman’s correlation analysis, it was confirmed that the increases of five bacterial strains and decreses of six bacterial strains were closely correlated with the increases of nine host metabolites and the decreases of another five host metabolites. Therefore, XAN can modulate the structure of gut microbiota in AD rats, the changes of gut microbiota were significantly correlated with endogenous metabolites, and symptom of AD was ultimately alleviated. Our findings suggest XAN may be a potential therapeutic drug for AD and the gut microbiota may be potential targeting territory of XAN via microbiome-gut-brain pathway.